An ECM-Mimetic Hydrogel to Promote the Therapeutic Efficacy of Osteoblast-Derived Extracellular Vesicles for Bone Regeneration - Man, Kenny; Brunet, Mathieu Y.; Federici, Angelica S.; Hoey, David A.; Cox, Sophie C. (Frontiers in Bioengineering and Biotechnology, 2022)
The use of extracellular vesicles (EVs) is emerging as a promising acellular approach for bone regeneration, overcoming translational hurdles associated with cell-based therapies. Despite their potential, EVs short half-life following systemic administration hinders their therapeutic efficacy. EVs have been reported to bind to extracellular matrix (ECM) proteins and play an essential role in matrix mineralisation. Chitosan and collagen type I are naturally-derived pro-osteogenic biomaterials, which have been demonstrated to control EV release kinetics. Therefore, this study aimed to develop an injectable ECM-mimetic hydrogel capable of controlling the release of osteoblast-derived EVs to promote bone repair. Pure chitosan hydrogels significantly enhanced compressive modulus (2.48-fold) and osteogenic differentiation (3.07-fold), whilst reducing gelation times (2.09-fold) and proliferation (2.7-fold) compared to pure collagen gels (P≤0.001). EV release was strongly associated with collagen concentration (R2>0.94), where a significantly increased EV release profile was observed from chitosan containing gels using the CD63 ELISA (P≤0.001). Hydrogel-released EVs enhanced human bone marrow stromal cells (hBMSCs) proliferation (1.12-fold), migration (2.55-fold) and mineralisation (3.25-fold) compared to untreated cells (P≤0.001). Importantly, EV-functionalised chitosan-collagen composites significantly promoted hBMSCs extracellular matrix mineralisation when compared to the EV-free gels in a dose-dependent manner (P≤0.001). Taken together, these findings demonstrate the development of a pro-osteogenic thermosensitive chitosan-collagen hydrogel capable of enhancing the therapeutic efficacy of osteoblast-derived EVs as a novel acellular tool for bone augmentation strategy.